Stress Triggers Dysmenorrhea in the Final Year Female Students - Putri Yuliantie (International Journal of Health Science and Technology, 2021)
The reproductive health of women is an essential component, several problems that can occur in the reproductive health of women, one of which is menstrual pain, this complaint is affected by psychological conditions. As a result, if it is not addressed immediately, it emerges the disruption in the routine and depression. The purpose of this study was to find out whether stress affects the occurrence of dysmenorrhea on the final year female students. The research method was the observational analytic with cross sectional approach. Sample consisted of 211 respondents, the analysis used was Kendal Tau. The result of the p-value was 0.000 and the contingency coefficient value was 0.378. It indicated that there was relationship between stress and dysmenorrhea in final year female students of Universitas ‘Aisyiyah Yogyakarta.